THE ROLE OF PODCASTS IN ENHANCING ENGLISH LANGUAGE SKILLS: A SYSTEMATIC LITERATURE REVIEW - Siti Aisah Ravita Dewi; Nurul Fadilah; Nafan Tarihoran (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
In the era of globalization, English language proficiency has become increasingly essential, leading to the adoption of innovative learning methods such as podcasts. This study explores the role of podcasts in enhancing English proficiency through a Systematic Literature Review (SLR) of academic sources published within the last five years. Using the PRISMA framework, 36 studies from 2020 to 2025 were analyzed from ResearchGate and Google Scholar. Articles were selected based on their relevance, research methods, and key findings on the impact of podcasts in English language learning. The results indicate that podcasts significantly enhance listening, speaking, and writing skills, improve vocabulary acquisition, and deepen cultural understanding. Additionally, they positively impact student motivation, provide flexible and accessible learning opportunities, and encourage active engagement. Podcasts are particularly effective in self-directed learning, allowing students to access content at their convenience, making them a valuable tool in technology-driven education. Furthermore, integrating podcasts into English curricula and training educators to maximize their use can enhance learning experiences and outcomes. These findings suggest that podcasts serve as an engaging and effective medium for language acquisition, fostering independent learning and improving overall proficiency. Therefore, their incorporation into modern teaching strategies is crucial for optimizing English language education.